A function-key driven syntax-directed editor for software systems design - Bassanino, Angelo Paulo (My University, 2014)
Program Description Language (PDL) is a high-level design language used for both hardware and software systems design. Due to the clerical effort involved in creating such a structured program, however, the PDL design is usually bypassed, and coding performed directly. The syntax-directed PDL generator package presented here, written in Pascal for the IBM-PC, is aimed at providing a tool for producing syntactically correct PDL programs with the minimum of effort. Function keys are used extensively for specifying system inputs, and PDL keywords are inserted via construct templates. Syntactical correctness is always enforced while indentation or prettypriuting is automatic. This userfriendly PDL editor thus encourages a top-down iterative design approach while automatically performing syntax and partial semantic error detection. It is believed that this much needed tool will not only promote high-level design principles, but also serve as the basis for automatic code generation for commonly used programming languages.
A project report submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg in partial fulfillment of the requirements for the degree of Master of Science in Engineering.